Associations between snus use, body mass index and general health in a cross-sectional population-based sample of women. Issue 5 (July 2018) - Lund, Ingeborg; Kvaavik, Elisabeth; Nygård, Mari; Hansen, Bo T.
Background: In Norway, snus use among women has increased substantially over the last decade, particularly in younger age groups. Snus use is associated with increased morbidity among men, but few studies have addressed health consequences of snus use among women. Aim: To investigate the associations between body mass index (BMI) and female snus use, and between self-rated general health and female snus use. Methods: A nationally representative net sample of 13, 756 women in Norway, aged 18–45 years, participated in a survey on lifestyle and health. Ordinal logistic regression was applied to address associations between snus use and BMI/general health, adjusting for age and lifestyle factors. Results: Compared to never users of snus, daily snus users had a lower likelihood of high BMI (OR: 0.83, 95% CI: 0.68–1.00), a higher likelihood of low BMI (OR: 1.63, 95% CI: 1.14–2.33), and a higher likelihood of poor/fair health (OR: 1.43, 95% CI: 1.08–1.90). Former and occasional snus users did not differ from never users in terms of BMI or general health in multiply adjusted models. Daily smokers had the highest likelihood of reporting poor/fair health (OR: 2.18, 95% CI: 1.8–2.63) relative to never smokers. Conclusions : Daily female snus use was associated with a lower likelihood of being overweight, and a higher likelihood of being underweight. Moreover, daily snus use was associated with a higher likelihood of worse general health. Former and occasional female snus use was not associated with BMI or general health.